Density and morfometric analysis of sia-sia (Sipunculus nudus) from Nusalaut island beach waters central Maluku - Adrianus Ferdinandus; Sintje Liline; Syahran Wael (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2022)
Sia-sia (Sipunculus nudus) has a shape resembling a worm, is an organism that usually lives in coastal areas, especially around seagrass areas, this biota tends to inhabit the bottom of the water especially in the substrate so that it is categorized as an infauna benthic organism and is able to inhabit areas with soft and hard substrates. This is a deskriptive type of research, to describe or describe information about the density and morphometrics of Sia-sia from the coastal waters of Nusalaut Island, Central Maluku. The results of the study on the density of Sia-sia on the island of Nusalaut, differ according to location, based on the results of the density calculation obtained. Each location shows the total average value of Absolute Density (KA) is 0,0063 ind/m2 (Low) and Relative Density (KR) is 100%. The Absolute density level (KA) in Abubu Vilage is 0,0068 ind/m2 (Low), the absolute density level (KA) in Ameth Villlage is 0,0064 ind/m2 (Low) and the absolute density level (KA) in Akoon Village is 0,0058 ind/m2 (Low), Based on the results of the Sia-sia morphometric research from Nusalaut Island, the Results vary from each village with Sia-sia morphometric average length of 12,14 cm, width 2,15 cm and weight of 31,6 g, followed by Akoon village with Sia-sia morphometric average length of 11.6 cm, width 2,21 cm, and a weight of 33,6 g, and the last one is Ameth Village with an average length of Sia-sia morphometric that is 13,02 cm, width 2,26 cm, and weight 36 g